EDUCATION MANAGEMENT CONTEST AT NAHDLATUL ULAMA BANGILAN ELEMENTARY SCHOOL, PASURUAN CITY AND BINA INSAN CENDEKIA ISLAMIC SCHOOL, PASURUAN CITY IN IMPROVING THE QUALITY OF STUDENTS - Syahrul Firmansyah; Dewi Masitah (International Journal of Multidisciplinary Reseach, 2025)
This study examines the contestation of educational management in two faith-based elementary schools in Pasuruan City: SD Unggulan Nahdlatul Ulama (NU) Bangilan and SDIT Bina Insan Cendekia. The research focuses on the management strategies applied and the ideological, structural, and cultural factors influencing their differences. Employing a qualitative approach with a multiple case study design, data were collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that SD NU Bangilan adopts a participatory-cultural management model emphasizing Ahlussunnah wal Jama’ah values, pesantren traditions, and community involvement. In contrast, SDIT Bina Insan Cendekia applies an integrated Islamic school management model that is systematic, disciplined, and indicator-based, supported by digital tools. The ideological orientation (NU vs tarbiyah), organizational structure, and school culture significantly shape distinct management patterns and influence student quality outcomes. In conclusion, the contestation between the two schools reflects not merely competition but also a constructive contribution of religious ideologies in fostering quality Islamic elementary education that is competitive and contextually relevant.